Implementation of the Policy on Functional Positions for Supervision of The Implementation of Regional Government Affairs at The Maybrat Regency Inspectorate of West Papua Province - Emanuelle S.R Pelealu; Fernandes Simangunsong; Dedeh Maryani (Utan Kayu Publishing, 2022)
The purpose of this research is to discover and analyze the implementation of functional position policies of PPUPD, discover and analyze the most determinant factor that affects the success and failure of functional position policies of PPUPD, as well to discover and analyze the mitigation of this implementation policies of PPUPD in the Inspectorate of Maybrat West Papua. The theory used for this approach came from Muchlis Hamdi (2017), that explained the implementation refers to three (3) indicator policies which is; Productivity, Linearity, and Efficiency. The methods used for this approach are Qualitatives, Data collection which includes interviewing, observation, documentation and examining the datum credibilities using triangulation of resources and techniques. The informans of this approach includes Regent of Maybrat, The Head of Regional House of Representatives of Maybrat, Regional Secretary of Maybrat, Asisten III of regional Secretariat of Maybrat, The Head of Regional Development Planning Agency of Maybrat, The Head of Regional Personnel Agency of Maybrat, The Inspecture of Maybrat, Assitant Inspector I of Inspectorate Maybrat, PPUPD of Inspectorate Maybrat, Treasurer of Public Works Office of Maybrat, Head of the BPK-RI Examination Team for West Papua Representatives and Contractors. Based on the field researches, we came to conclusions that the implementation functional position of PPUPD in Maybrat Inspectorate has not been fully applied, as the development of the PPUPD potential manpower, limitations of assets, funds and technologies, inadequate budget and technology, and uncooperative OPD in participating the audits conducted by the PPUPD Inspectorate of maybrat district. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis Implementasi Kebijakan Jabatan Fungsional Pengawas Penyelenggaraan Urusan Pemerintahan Daerah, mengetahui dan menganalisis faktor yang paling determinan mempengaruhi keberhasilan dan ketidakberhasilan Implementasi Kebijakan Jabatan Fungsional Pengawas Penyelenggaraan Urusan Pemerintahan Daerah, serta mengetahui dan menganalisis Upaya mengatasi ketidakberhasilan Implementasi Kebijakan Jabatan Fungsional Pengawas Penyelenggaraan Urusan Pemerintahan Daerah di Inspektorat Kabupaten Maybrat Provinsi Papua Barat. Adapun teori yang dipakai sebagai pisau analisis dalam penulisan tesis ini adalah teori dari Muchlis Hamdi (2017) yang menjelaskan bahwa Implementasi dilihat pada 3 (tiga) indikator dalam pengimplementasian kebijakan yaitu Produktivitas, Linearitas dan Efisiensi. Metode yang digunakan pendekatan kualitatif, teknik pengumpulan data adalah wawancara, observasi , dokumentasi dan menguji kredibiltas data dengan menggunakan triangulasi sumber dan teknik. Adapun informan dalam penelitian ini adalah Bupati Maybrat, Ketua DPRD Maybrat, Sekretaris Daerah Maybrat, Asisten III Setda Maybrat, Kepala Bappeda Maybrat, Kepala BKPSDM Maybrat, Inspektur Maybrat, Irban I Inspektorat Maybrat, PPUPD Inspektorat Maybrat, Bendahara Dinas PU Maybrat, Ketua Tim Pemeriksaan BPK-RI Perwakian Papua Barat, Pihak Ketiga. Berdasarkan hasil penelitian dilapangan dapat disimpulkan bahwa Implementasi Kebijakan Jabatan Fungsional PPUPD di Inspektorat Maybrat belum dilaksanakan secara maksimal dikarenakan belum dilakukan Pengembangan Potensi SDM PPUPD, Keterbatasan dalam pemanfaatan Sumber daya Aset, Dana dan Teknologi serta OPD yang kurang kooperatif dalam mengikuti Audit oleh PPUPD Inspektorat Kabupaten Maybrat.